Evaluation of Sex Differences in Cannabinoid Dependence - Marusich, Julie A. (2014)
BACKGROUND: Chronic recreational marijuana users often report withdrawal symptoms when trying to quit, with some reports suggesting withdrawal may be more pronounced in women. In animal models, female rodents show enhanced sensitivity to acute Δ(9)-tetrahydrocannabinol (THC) administration, but chronic administration has been studied little. METHODS: Sex differences in THC dependence in rats were examined. Adult male and female Sprague-Dawley rats were administered 30 mg/kg THC or vehicle twice daily for 6.5 days. On day 7, rats were challenged with vehicle or rimonabant, counterbalanced across dosing groups, and were assessed for withdrawal-related behaviors. RESULTS: During chronic THC dosing, disruption of estrous cycling and weight loss (both sexes) were observed. Whereas overt signs of withdrawal were minimal in THC-treated rats challenged with vehicle, rimonabant precipitated a pronounced withdrawal syndrome in THC-dependent rats that was characterized by changes in a number of domains, including somatic (paw tremors, head twitches, and retropulsion), early-stage cognition (lack of locomotor habituation, disrupted prepulse inhibition), and affective (increased startle reactivity). With the exception of increased retropulsion in female rats, sex differences were not noted. In vehicle-treated rats, rimonabant induced puritis. CONCLUSIONS: This study represents the first examination of THC dependence in adult rats of both sexes, extends previous findings to females, and revealed some sex differences. The results suggest that the changes that occur during precipitated withdrawal from THC extend beyond somatic signs to more nuanced disruptions of cognitive and affective functioning. The breadth of withdrawal signs observed in rodents mirrors those that have been observed in humans.